2010
DOI: 10.1002/anie.201003959
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of a Surface Quenching Effect on Size‐Dependent Luminescence of Upconversion Nanoparticles

Abstract: Lanthanide-doped upconversion (UC) nanoparticles have shown considerable promise in biological labeling, imaging, and therapeutics.[1] However, although current synthetic approaches allow for preparation of ultrasmall UC nanoparticles with precise control over particle morphology and emission color, [2] smaller nanoparticles come at the expense of weaker emissions, which is a constraint that is practically impossible to surpass. Many fundamental aspects of the UC luminescence in these nanomaterials still lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
572
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(609 citation statements)
references
References 78 publications
28
572
0
2
Order By: Relevance
“…An approximate 450-fold enhancement in the overall UC emission intensity of coreshell NaGdF 4 :Yb/Tm/NaGdF 4 by particles was observed due to surface passivation. [118] Further, the authors demonstrated a novel design based on a combination of core-shell NaYF 4 :Yb/Tm@NaYF 4 upconverting nanoparticles and manganese dioxide nanosheets that was expected to find application in the rapid and selective detection of glutathione in aqueous solutions and living cells. [119] A drastic enhancement in the UC luminescence of BaGdF 5 :Yb 3 + /Er 3 + core-shell nanoparticles was reported.…”
Section: How Do the Core-shell Structures Tune Uc Emission?mentioning
confidence: 99%
“…An approximate 450-fold enhancement in the overall UC emission intensity of coreshell NaGdF 4 :Yb/Tm/NaGdF 4 by particles was observed due to surface passivation. [118] Further, the authors demonstrated a novel design based on a combination of core-shell NaYF 4 :Yb/Tm@NaYF 4 upconverting nanoparticles and manganese dioxide nanosheets that was expected to find application in the rapid and selective detection of glutathione in aqueous solutions and living cells. [119] A drastic enhancement in the UC luminescence of BaGdF 5 :Yb 3 + /Er 3 + core-shell nanoparticles was reported.…”
Section: How Do the Core-shell Structures Tune Uc Emission?mentioning
confidence: 99%
“…Despite many studies on the spectral properties of UCLNPs, it is rather surprising that the quenching of their luminescence by heavy metal (HM) ions has not been investigated so far. It is known that UCLNPs undergo surface-quenching effects associated with the size-dependent luminescence, [43] but this is not related to external quenchers. We report here, for the first time, that the luminescence of UCLNPs nanocrystals is strongly quenched by HM ions.…”
Section: Introductionmentioning
confidence: 99%
“…10 nm diameter) UCNPs [86][87][88]; however, the small particle size increases solvent quenching, especially by OH and NH groups, owing to the sizable percentage of the lanthanoid emitters that are at or near the surface in such species. Such quenching may be reduced by growing a shell of unsubstituted host material around the UCNP [89,90] to isolate surface ions from these environmental effects. Related modifications of UCNPs include silica or polymer coatings [91][92][93][94][95][96][97][98].…”
Section: Uncaging Using Upconversion Nanoparticles (A) Introduction Tmentioning
confidence: 99%